2020
DOI: 10.1186/s13046-020-01598-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcription activation of circ-STAT3 induced by Gli2 promotes the progression of hepatoblastoma via acting as a sponge for miR-29a/b/c-3p to upregulate STAT3/Gli2

Abstract: Background: Hepatoblastoma (HB) is a common liver malignancy in children. Our previous study has disclosed the crucial role of STAT3 (signal transducer and activator of transcription 3) in HB. Aim of the study: Present study was designed to study the circular RNA (circRNA) STAT3 in HB. Methods: Gel electrophoresis revealed the circular characteristics of circ-STAT3. Function assays like EdU, transwell and sphere formation assay disclosed the function of circ-STAT3 in HB cells. Mechanism assays including ChIP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…Another feedback interaction was also reported in hepatoblastoma [ 130 ]. In particular, circ-STAT3 is transcriptionally activated by GLI2, and at the same time, GLI2 and STAT3 are both upregulated due to circ-STAT3 binding miR-29-3p isomiRs.…”
Section: Circrna-mediated Regulation Of Major Signaling Pathwaysmentioning
confidence: 67%
See 1 more Smart Citation
“…Another feedback interaction was also reported in hepatoblastoma [ 130 ]. In particular, circ-STAT3 is transcriptionally activated by GLI2, and at the same time, GLI2 and STAT3 are both upregulated due to circ-STAT3 binding miR-29-3p isomiRs.…”
Section: Circrna-mediated Regulation Of Major Signaling Pathwaysmentioning
confidence: 67%
“…Moreover, an increasing number of studies emphasize the participation of circRNAs in the regulation of signaling pathways linked to cancer stem cells (CSCs) [ 130 ]. CSCs are vital for tumor progression, since they promote growth and are responsible for metastatic spread, relapses, and treatment failure.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In general, circular RNAs (circRNAs) can modulate gene expression by acting as sponges of endogenous miRNAs. It has shown that circ-HIPK3, circ_0076305 and circ-STAT3 positively modulate STAT3 signaling by sponging miR-124-3p, miR-296-5p, and miR-29a/b/c-3p, respectively [ 36 38 ]. In parallel, STAT3 has a capacity of regulating ncRNAs directly or indirectly.…”
Section: The Stat3 Signaling Pathwaymentioning
confidence: 99%
“…15 Recent studies have shown that several cytoplasmic circRNAs can regulate the expression of transcriptional factors. [26][27][28] A study in 2018 showed that circITGA7 could promote the transcription of its host gene ITGA7 by suppressing the transcription factor RREB1 via the Ras pathway. 26 Chia et al 27 have suggested that circ-DAB1 upregulates the expression of recombination signal-binding protein for the immunoglobulin kappa J region (RBPJ), an important transcriptional factor in the NOTCH pathway, to activate the parental gene DAB1 transcription.…”
Section: Circrnas Regulate the Transcription Of Parental Genesmentioning
confidence: 99%
“…52 More recently, circ-STAT3 was also found to elevate STAT3 expres-sion by upregulating the transcription factor Gli2 via sponging miR-29a/b/c-3p. 28 Studies cited above illustrate that circRNA can regulate the transcription of its parental gene and impact distinct steps in the transcription cycle. Given that both cytoplasmic and nuclear circRNAs are involved, transcriptional control could represent a more general role of circRNAs than is currently appreciated.…”
Section: Circrnas Regulate the Transcription Of Parental Genesmentioning
confidence: 99%